L’héritage d’Alfred Kiyana et l’énigme des paquets cérémoniels meskwaki - Emmanuel Désveaux (Journal de la Société des Américanistes)
Alfred Kiyana’s legacy and the enigma of Meskwaki sacred bundles. At the beginning of the 20th century, Alfred Kiyana entrusted the anthropologist Michelson with the liturgical text related to a so-called sacred bundle. He equally sold him the bundle itself which found its way into the reserves of the ethnographical museum of Berlin, presently located in Dahlem. Recently, the linguist Ives Goddard has presented a new translation of the text. The first section of the present paper proposes a comment of this long text which aims at revealing its mythical background, its ritual implications, and the links to its material counterpart, i. e. the content of the bundle kept in Dahlem. In the second section the commentary attempts a better understanding of the underlying principles of Meskwaki social organization, notorious for its high opacity. The bundle complex appears as an anti-gestational act, merely masculine and saturated with death’s motives, which stands in a transformational relationship with the overall features of Algonquian totemism. As a conclusion, the commentary raises the question whether the bundle complex does give the Meskwaki a specific awareness of the passing of time, in other words, of history.